Germination response of three Argentinian Prosopis species to osmotic priming - Ruiz, Mónica Beatriz (2012)
Prosopis is a widely distributed genus with 13 species endemic to Argentina. Several of these are harvested for multiple uses. The regeneration of this specie can only be achieved through the implantation of seedlings or direct sowing of seeds. High rate and percentages of germination are key factors affecting the success of reintroduction of these species. Among the treatments used to enhance germination and emergence rate the osmotic priming (imbibition of seeds in osmotic solutions) is one of the most successful. In the present study we investigate the effect of osmotic priming on seed germination rate and germination percentage for three species of Prosopis (P. Argentina, P. chilensis and P. flexuosa). We subjected mechanically scarified seeds of each species to 16 treatments resulting from the combination of PEG solutions with four osmotic potentials (-0.8; - 1.0; -1.2 and -1.4MPa) during four time periods (24, 48, 72 and 96h). Treatment seeds were contrasted against a control consisting of scarified seeds. The osmotic priming significantly increased germination rate and radicle length relative to control seeds for three species. The effectiveness of priming treatments in enhancing germination of native Prosopis species constitutes a significant achievement that may well increase the success of reforestation programs.